Lifesaver boy - Airyn (2016)
Lifesaver Boy is a 2D hand-drawn animated short film. It narrates on the story of a little boy who dreams to become a lifeguard as he is inspired from an article in the magazine. Eventually he discovers another way to become a lifesaver.